The Candida albicans Exocyst Subunit Sec6 Contributes to Cell Wall Integrity and Is a Determinant of Hyphal Branching - Chavez-Dozal, Alba A. (Eukaryot Cell, 2015)
The yeast exocyst is a multiprotein complex comprised of eight subunits (Sec3, Sec5, Sec6, Sec8, Sec10, Sec15, Exo70, and Exo84) which orchestrates trafficking of exocytic vesicles to specific docking sites on the plasma membrane during polarized secretion. To study SEC6 function in Candida albicans, we generated a conditional mutant strain in which SEC6 was placed under the control of a tetracycline-regulated promoter. In the repressed state, the tetR-SEC6 mutant strain (denoted tSEC6) was viable for up to 27 h; thus, all phenotypic analyses were performed at 24 h or earlier. Strain tSEC6 under repressing conditions had readily apparent defects in cytokinesis and endocytosis and accumulated both post-Golgi apparatus secretory vesicles and structures suggestive of late endosomes. Strain tSEC6 was markedly defective in secretion of aspartyl proteases and lipases as well as filamentation under repressing conditions. Lack of SEC6 expression resulted in markedly reduced lateral hyphal branching, which requires the establishment of a new axis of polarized secretion. Aberrant localization of chitin at the septum and increased resistance to zymolyase activity were observed, suggesting that C. albicans Sec6 plays an important role in mediating trafficking and delivery of cell wall components. The tSEC6 mutant was also markedly defective in macrophage killing, indicating a role of SEC6 in C. albicans virulence. Taken together, these studies indicate that the late secretory protein Sec6 is required for polarized secretion, hyphal morphogenesis, and the pathogenesis of C. albicans.